Seipin Deficiency Accelerates Heart Failure Due to Calcium Handling Abnormalities and Endoplasmic Reticulum Stress in Mice - Wu, Xiaoyue; Liu, Xuejing; Wang, Huan; Zhou, Zihao; Yang, Chengzhi; Li, Zijian; Zhang, Youyi; Shi, XiaoLu; Zhang, Ling; Wang, Yuhui; Xian, Xunde; Liu, George; et al. (Frontiers in Cardiovascular Medicine, 2021)
Seipin deficiency can induce hypertrophic cardiomyopathy and heart failure, which often lead to death in humans. To explore the effects and the possible mechanisms of Seipin deficiency in myocardial remodeling, Seipin knockout (SKO) mice underwent transverse aortic constriction (TAC) for 12 weeks. We found more severe left ventricular hypertrophy and diastolic heart failure and increases in inflammatory cell infiltration, collagen deposition and apoptotic bodies in the SKO group compared to those in the wild type (WT) group after TAC. Electron microscopy also showed more extensive sarcoplasmic reticulum expansion, deformation of microtubules and formation of mitochondrial lesions in the cardiomyocytes of SKO mice than in those of WT mice after TAC. Compared with the WT group, the SKO group showed increases in endoplasmic reticulum (ER) stress-, inflammation- and fibrosis-related gene expression, while calcium ion-related factors, such as Serca2a and Ryr, were decreased in the SKO group after TAC. Increased levels of the ER stress-related protein GRP78 and decreased SERCA2a and P-RYR protein levels were detected in the SKO group compared with the WT group after TAC. Slowing of transient Ca2+ current decay and increased SR Ca2+ content in myocytes were detected in the cardiomyocytes of SKO mice. Adipose tissue transplantation could not rescue the cardiac hypertrophy after TAC in SKO mice. In conclusion, we found that Seipin deficiency could promote cardiac hypertrophy and diastolic heart failure after TAC in mice. These changes may be related to the impairment of myocardial calcium handling, ER stress, inflammation and apoptosis.